Orthogonal activation of propargyl and n-pentenyl glycosides and 1,2-orthoesters - Vidadala, Srinivasa Rao; Thadke, Shivaji A.; Hotha, Srinivas (Journal of Organic Chemistry, 2009)
An orthogonal activation strategy with propargyl and n-pentenyl glycosides has been identified. According to this methodology, n-pentenyl glycosides can be selectively activated with NIS/TMSOTf in the presence of either armed or disarmed propargyl O-glycosides. In addition, we report herein that propargyl 1,2-orthoesters can be selectively activated with AuBr(3) in CH(2)Cl(2) at room temperature in the presence of n-pentenyl glycosides. Similarly, pentenyl 1,2-orthoesters can be selectively activated with NIS/Yb(OTf)(3) in the presence of propargyl glycosides.

Gold-catalyzed glycosidations: synthesis of 1,6-anhydro saccharides - Thadke, Shivaji A.; Hotha, Srinivas (Tetrahedron Letters, 2010)
Various 1,6-anhydro sugars are synthesized utilizing salient features of gold-catalyzed glycosidations. All the reactions occurred under mild conditions in the presence of 7 mol % of AuBr(3) enabling easy synthesis of 1,6-anhydro sugars from corresponding 6-hydroxy propargyl/methyl monosaccharides, disaccharides, and trisaccharides in good yields. (C) 2010 Elsevier Ltd. All rights reserved.

Gold catalyzed glycosidations for the synthesis of sugar acrylate/acrylamide hybrids and their utility - Thadke, Shivaji A.; Kar, Mritunjoy; Sen Gupta, Sayam; Hotha, Srinivas (Carbohydrate Research, 2011)
Propargyl glyco 1,2-orthoesters were exploited for the efficient synthesis of interesting glycomonomers such as glyco-acrylates and acrylamides using gold catalysts. It was observed that propargyl glyco 1,2-orthoesters with hydroxyethyl acrylates gives very good yield of the corresponding glyco-acrylates in a single step in the presence of catalytic amount of gold(III) catalyst; whereas, gold catalyzed glycosidation reaction on hydroxyethyl acrylamides was found to yield the corresponding acrylamidoyl 1,2-orthoester which was then converted to the corresponding glycol-acrylamide in the presence of catalytic amount of TMSOTf. Synthesized glyco-acrylate/acrylamide monomers are shown to undergo thiolate addition as well as free radical polymerization (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: carbohydrates; Glycoacrylamides; Glycoacrylates; Glycopolymers; glycosylation; Gold